Linguistic Strategies of Learning Persian Language to Kurdish Learners - Ahmad Qadir, Zahra; Ali Rahman, Layla (Zanco Journal of Human Sciences, 2023)
The present study is entitled "Linguistic Strategies of Learning Persian Language to Kurdish Learners". It aims to examine the role of learning strategies (direct and indirect language strategies) in second language teaching and their relationship with second language teaching and learning plans. The participants for this study consist of students of the Persian language department of both Salahaddin and Sulaymaniyah universities and students of the Kurdish language departments of the state universities of the Iraqi Kurdistan region. To conduct the study, a questionnaire of (50) questions was prepared in Kurdish Sorani dialect. A total number of completed questionnaires that the researchers received reached (474). Regarding the process of circulating the questionnaire, it was provided to the universities electronically, and the participants filled out voluntarily. These participants were 127 males and 347 females. They were undergraduate students from first to fourth academic years. Importantly, the questionnaire was prepared by both researchers based on the teaching and learning plans, many years of experience in this field, the guidelines of Oxford questionnaire design and the learning instruction plans proposed by Omali and Chamut. The results showed that linguistic strategies have a direct relation to second language learning. Their mother tongue of all the participants is Kurdish. Gender variable is one of the effective factors in the language learning in a way that the relationship between the memory related process learning strategies varies from female to male. Moreover, based on the direct and indirect strategies of language learning, self-learning and the working environment of the learners have a significant impact on second language learning. As it can be seen in the questionnaire, there is a strong connection and coordination between the strategies.